Siete dibujantes - Martínez Plasencia, Ramiro; Morales Galicia, Diana; Ledezma, Miguel; Hernández, Octavio Irving; Bastarrachea Sabido, Adrián; Zúñiga, Ernesto; Guisande, Selma (El Ornitorrinco Tachado. Revista de artes visuales, 2018)
Dossier